PENGARUH TADARUS AL QUR’AN TERHADAP ETIKA SISWA DI SMK ISLAM NURUL HIKMAH SANGATTA UTARA - Aprianti Astuti; Eko Nursalim; Abdul Khadir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background of this research is rooted in the urgency of building students' morality through consistent religious activities, particularly Quran recitation. The practice of Quran recitation is not merely a textual literacy routine, but rather a strategic medium for internalizing Islamic doctrine that has a systemic impact on the character construction and ethics of students. This study has the objective of measuring the magnitude of the influence of Quran recitation on student ethics at SMK Islam Nurul Hikmah Sangatta Utara. The research approach taken is quantitative by implementing a simple linear regression method. The study population included 91 grade XI students, where the sample determination was carried out using a saturated sampling technique, so that all population entities were involved as subjects. The data collection procedure was carried out through observation, distribution of questionnaires with a Likert scale, and documentation studies. The research findings confirm the positive and significant contribution of Quran recitation activities to students' ethical behavior. Instrument validation shows a Cronbach Alpha reliability value for variable X of 0.872 and variable Y of 0.883, which is in the category range of 0.800 to 1.000, thus indicating a very strong level of consistency. The resulting regression equation is Y = 22.274 + 0.706X, which reflects the reliability of the data. The correlation coefficient or R was recorded at 0.747, indicating a strong correlation between the variables. The coefficient of determination or R Square value of 0.558 explains that Al-Quran recitation contributes 55.8 percent to the variation in student ethics. Based on the hypothesis test, the calculated t value obtained was 10.600, exceeding the t table of 1.987 at a significance level of 5 percent with a p value <0.001. These results form the basis for accepting the alternative hypothesis or Ha and rejecting the null hypothesis or H0.